2022
DOI: 10.1007/s10336-022-02004-0
|View full text |Cite
|
Sign up to set email alerts
|

First genetic data for the critically endangered Cuban endemic Zapata Rail Cyanolimnas cerverai, and the taxonomic implications

Abstract: The taxonomic affinity of the near-flightless Zapata Rail Cyanolimnas cerverai, a critically endangered and highly localized species endemic to Cuba, has long been debated. Morphological analyses have suggested that this species, which constitutes a monotypic genus, could be related either to the extinct Tahitian Cave Rails (Nesotrochis sp.) or to the South American rail tribe Pardirallini, i.e., the genera Neocrex, Mustelirallus, and Pardirallus. While pronounced phenotypic convergence—and divergence—among ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Under the heading Family RALLIDAE: Rails, Gallinules, and Coots, add the following to the existing Notes: Linear sequence of Pardirallus and Mustelirallus follows Kirchman et al (2021) and Brown et al (2022). Notes.-Rufirallus schomburgkii was formerly placed in Micropygia, but genetic data (Kirchman et al 2021, Depino et al 2023 show that this species is sister to Rufirallus viridis (Müller, 1776) [Russet-crowned Crake].…”
Section: [P 271]mentioning
confidence: 99%
See 3 more Smart Citations
“…Under the heading Family RALLIDAE: Rails, Gallinules, and Coots, add the following to the existing Notes: Linear sequence of Pardirallus and Mustelirallus follows Kirchman et al (2021) and Brown et al (2022). Notes.-Rufirallus schomburgkii was formerly placed in Micropygia, but genetic data (Kirchman et al 2021, Depino et al 2023 show that this species is sister to Rufirallus viridis (Müller, 1776) [Russet-crowned Crake].…”
Section: [P 271]mentioning
confidence: 99%
“…3 . [p. 135] Phylogenetic analyses of nuclear and mitochondrial DNA sequences have shown that the genera Neocrex and Cyanolimnas are very closely related to extralimital species Mustelirallus albicollis (Garcia-R et al 2014, 2021; Kirchman et al 2021; Brown et al 2022). These findings result in the following changes:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, representatives of Amaurolimnas and Mustelirallus crakes were placed together with the Aramides wood rails and Pardirallus rails in the ‘ Aramides ’ clade (sensu Garcia‐R et al, 2014a) or tribe Pardirallini (sensu Kirchman et al, 2021, 2022). Additionally, new results from historic DNA indicate that the Zapata Rail ( Cyanolimnas cerverai ) belongs to this ‘ Aramides ’ clade or tribe Pardirallini, closely related to Mustelirallus crakes (Brown et al, 2022). Another species, the Sora ( Porzana carolina ), formerly called Sora Crake, belongs to a clade with coots and moorhens (the ‘ Fulica ’ clade, sensu Garcia‐R et al, 2014a, 2020; tribe Fulicini, sensu Kirchman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%